Performance of Oxfendazole in Nematode-Infected Post-Weaning Lamb on Pasture - Hastuti, S; Samsi, M (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2010)
A study was conducted to determine the effectiveness of drug anthelmintic intensity oxfendazole against gastrointestinal nematode worm infections in weaned lambs. Experiments conducted on 18 lambs weaned off, randomly divided into 3 groups namely P0: grazed sheep, untreated as controls, P1: grazed sheep treated with oxfendazole, and P2: un-grazed sheep, not treated with oxfendazole. The total worm eggs per gram (TEG) in the feces until 9 weeks before treatment 9 with no significant differences (P<0.05) and up to week 12 was not significantly different (P>0.05), means that the grazing treatment oxofendale treatment have real impact on the intensity of infection at week 9 post-treatment. This is related to the maturing of young worms and the intensity of infection depends on the influence of time outside the body of sheep. Of total plasma protein (TPP) and packed cell volume (PCV) until week 12 showed that antibiotic treatment measures and grazing is very real effect (P<0.01), between the treatment group P1 with different P0 is very real (P<0,01), between P2 with different P0 very real (P<0.01) and between P1 and P2 is not significantly different (P>0.05). Means treatment with oxfendazole helminthic very real effect on total plasma protein and packed cell volume in both the shepherd and the sheep who did not shepherd. (Animal Production 12(1): 39-43 (2010)Key Words: oxfendazole, grazing and gastrointestinale nematod